Strategi Pembelajaran IPS dalam Pengembangan Keterampilan Sosial di Indonesia : Analisis Bibliometrik - Asep Asep (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
The development of social skills is one of the fundamental objectives of Social Studies (IPS) learning in shaping adaptive, characterful students who are able to actively participate in social life. This study aims to analyze the trends, focus, methodology, and learning strategies of SSE used in developing students' social skills in Indonesia. The study uses a bibliometric analysis and quantitative-descriptive approach to 60 scientific publications published between 2013 and 2025. The results show exponential growth in publications, with around 90% of articles concentrated in the period 2023–2025, indicating increased academic awareness of the urgency of social skills in social studies learning. In terms of education levels, the research was dominated by the elementary school context (60%), while junior high and high school levels were still relatively minimal, indicating a significant research gap. Methodological analysis reveals the dominance of qualitative approaches (40%), followed by literature reviews (20%), while experimental research is still limited. From a pedagogical perspective, active learning strategies, particularly Project-Based Learning and Problem-Based Learning, dominate the study with a proportion of around 45%, followed by cooperative learning, differentiated learning, technology integration, and local wisdom. These findings confirm that the development of social skills in social studies learning is most effective when integrating active learning, socio-cultural contexts, and technological support. This study provides important implications for the development of evidence-based social studies learning practices and opens up opportunities for further research at the secondary education level with a stronger methodological design.